Evaluating the Process of Arabic Translation of the Words in the Book "Imamat va Rahbari" (Imamate and Leadership) Based on Ladmiral's Theory - Narges Samareh; Vahideh Motahari; Reyhaneh Mollazadeh (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2023)
Jean-René Ladmiral, a French theoretician, proposed components for the translation of words that are helpful for the translator in the process of conveying meaning and creating a balance between the words of the target text or the source text. In this article, the performance of the translator in the Arabic translation of the words of the book Imamat va Rahbari and the quality of the translation have been evaluated based on Ladmiral's model and with descriptive-analytical and statistical methods. The findings of the research show that the translator tries to convey the meaning of the words through matters such as the selection of the translator, disambiguation, minimal interpretation, and addition, and provides a comprehensible and readable translation. In many cases, words have been borrowed. Sometimes, due to the inappropriate deletion of words and inappropriate selection of equivalents, the translator has not been able to recreate the content of the message for the audience, and therefore requires revision and re-editing.Keywords: Evaluation of Translation, Javad Ali Kassar, Imamat va Rahbari Book, Morteza Motahari, Ladmiral's Theory.  IntroductionWith the scientific advances that are expanding in the world, to achieve the scientific and cultural achievements of societies, the translation of texts is essential. Along with the translation of texts, its evaluation also prospered and gradually took a scientific form and was able to eliminate many shortcomings of translations and by providing effective solutions, it became a path for future translators.Due to the innate need of mankind for religion, translators in every era have tried to translate holy texts into different languages and provide the basis for the development of religious thought. The translator of religious texts always faces challenges, one of which is vocabulary balance. In the field of religion, words are used that have a special cultural meaning, and if the translator cannot find an exact equivalent in the dictionary to convey their meaning, he uses the explanatory strategy of words or a close equivalent in the target language, and sometimes the translator prioritizes vocabulary borrowing.Among these texts is the book "Imamat va Rahbari" by Shahid Morteza Motahari, which was translated into Arabic by Iraqi religious researcher and translator Javad Ali Kassar. In this thesis, the most important tool of translation, namely "scientific criticism and evaluation", is used to measure the translator's performance in the way of transferring words. For the application of this criticism, Ladmiral’s model was chosen because the useful solutions of this model are very helpful for the translator in order to convey the meaning of the words and provide a good translation.Therefore, after explaining Ladmiral's theory about the process of word transfer, the present research examines the performance of the translator and the quality of the translation by comparing two Persian and Arabic texts and expressing their differences and similarities. For this purpose, the present research seeks to answer the following questions::How does the translator perform in transferring words to Arabic based on Ladmiral's model?How did the methods used by the translator to convey the meaning of the words have an effect on improving the translation?Literature ReviewFew research studies about the evaluation of the lexical process based on Ladmiral's model are as follows:- The article "Lexical Balance and its Importance in Detailed Understanding of the Text (Case Study of Five Persian Translations Of Nahj ul-Balaghah Sermons) " by Seyyed Mehdi Masbouq and others (2014).- The article "Induction of Translation of the Story of "Thousand and One Nights" by Abdellatif Tasouji Based on the Pattern of Jean-Rene Ladmiral" by Shahram Delshad, and others (2015).- The article "Evaluation of the translation process of Nahj al-Balaghah words based on the theory of Jean René Ladmiral" by Ali Syadani and colleagues (2016).- The article A Critical Review of Mohammad Dashti's Translation of Nahj al-Balāghah (Arabic: نهج ٱلبلاغه‎) Based on Ladmiral’s Model (1994) by Askar Babazadeh and others (1400).The difference between the present research and the mentioned studies is that so far no criticism and evaluation has been done for the Arabic translation of the words of the book "Imamat va Rahbari" by Morteza Motahari.MethodologyThis research has been written with a descriptive-analytical and statistical method and using library tools. To collect information, the thirty-third edition of the book "Imamat va Rahbari" (164 pages) and the second edition of the book "Al-Imamat" (234 pages) were compared based on Ladmiral's theory, and by using Excel software, the frequency of components of Ladmiral was obtained. Then, by extracting the statistical data and analyzing them, the performance of the translator in the transfer of words and the quality of the translation was determined.ConclusionThe findings of this research are:1- The translator has a more audience-oriented attitude and tries to convey the meaning to the audience at any cost.2- In transferring the words, the translator has tried to choose an appropriate equivalent from among the many equivalents found in the dictionaries, and if no appropriate equivalent has been found in the dictionary, he starts with minimal interpretation and explanatory additions in the form of nominal, adverbial, verbal, etc. in order to convey the semantic layers of the word to the audience, and sometimes he chooses an equivalent according to the context by his own discretion, and when there is no lexical equivalent and even with minimal interpretation, the implied meaning of the word is not conveyed to the audience, he transferred those words to the target language in the form of borrowing.3- Sometimes, by choosing inappropriate equivalents and inappropriate omissions of words, he has not provided a readable and acceptable translation.4- To fix the inappropriate translation of some words, it is better for the translator to review and re-edit.